Gestão da renda familiar de mulheres assentadas: processos educativos e suas tensões - Freitas, Mariana Machitte de (Universidade Federal de São Carlos, 2020)
This research aimed to understand and analyze the educational processes resulting from the family income management carried out by women beneficiaries of the Bolsa Família Program (PBF), residents of the Nova São Carlos Agrarian Community Settlement Project, located in the city of São Carlos / SP. Our theoretical and methodological framework of study understands that educational processes arise from the experience of people in various social practices, with family income management being an action that involves administration practices intermediated by money, but also by exchanges, donation, self-consumption and sale of the production obtained from the land. Studies on poverty, gender and the feminization of poverty went through the theoretical foundation and analysis of the data carried out. The research, of qualitative nature, used for the data collection the methodology of the participant observation, as well as the accomplishment of reflective interviews with 6 settled women and beneficiaries of the PBF. The data analysis was based on the Content Analysis technique, from which 3 thematic categories were found. “It has to work”: the woman in money management, who presents in a detailed way the financial income management carried out by settled women and the educational processes resulting from this. “Land is everything for me”: the woman in land management, who debates the educational processes of income management linked to land use and management, self-consumption and the division of labor. “I want to know if I have rights”: the woman struggling for access to Social Rights, which indicates the educational processes resulting from the access or not to social rights and its impact on the (inter) subjectivity of these women, as well as its consequences for the maintenance and deepening of the conditions of poverty experienced in the settlement. As a result of the research, we affirm that the income management of settled women has been taking place in the process of fighting for the right to land, for the right to live on the land and from the land. Fight towards liberation, humanization, overcoming limit situations in the form of resistance and persistence. These are educational processes produced by the tension between the dehumanization imposed by social conditions and the process of seeking liberation, which, for them, means living on the land.
Gestión de la renta familiar de mujeres asentadas: procesos educativos e sus tensiones
Family income management of settled women: educational processes and its tensions
Keywords: Processos educativos; Gestão da renda familiar; Programa Bolsa Família; Gênero; Reforma Agrária; Educational processes; Family income management; Bolsa Família Program; Gender; Agrarian Reform; CIENCIAS HUMANAS::EDUCACAO